Post "Post‐Truth": Are We There Yet?. Issue 4 (13th August 2019) - Haack, Susan
Abstract: After explaining why, after dealing with post‐modernist confusions about truth in various books and articles from the mid‐1990s to, most recently, 2014 (§1), Haack returns to the topic of truth. She begins (§2) with some thoughts about the claim that concern for truth is on the decline, and perhaps at a new low; a claim that, sadly, may well be true. Then (§3) she looks at some of the many forms that carelessness with the truth may take, and shows that, so far from revealing that the concept of truth is seriously problematic or that there is no such thing as objective truth, it simply makes no sense to say that lies, half‐truths, etc., are ubiquitous unless there is such a thing as truth, and a legitimate truth‐concept. After that, (§4) she argues that, of course, there is such a thing as objective truth, and a robust truth‐concept. And finally, (§5) she suggests some ways to fight against the rising tide of unconcern for truth—and gives her answer to the (trick) question in her subtitle.